2012
DOI: 10.1002/oa.1189
|View full text |Cite
|
Sign up to set email alerts
|

Legg–Calvé–Perthes Disease and unifocal eosinophilic granuloma in a visigoth from the Duratón necropolis (Segovia, Spain)

Abstract: Individual number 12, exhumed at the Durató n Visigoth necropolis (Segovia, Spain), was found in a supine position inside a simple fossa without adornments. He was a very robust adult ($50/60 years) male presenting two pathologies, independently originated and both occurring in a particular anatomical area: the right hip. The first one has been diagnosed as Legg-Calvé-Perthes Disease, and it affects the right femur and the coxal.The femoral head has a diameter that is much greater than usual, with a porous art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Osteomyelitis cannot be ruled out as a cause for the bony changes in the lower leg, but is also not evident, as there are no cloacae visible. Herrerín and Garralda (2012) report a case of LCPD with an atrophied ipsilateral tibia; the smaller diameter and shorter length of the ipsilateral tibia in the case of SHSM22 could have a similar origin. There is also a small but pronounced enthesophyte on the medial side of the proximal shaft of the left tibia.…”
Section: Discussionmentioning
confidence: 88%
“…Osteomyelitis cannot be ruled out as a cause for the bony changes in the lower leg, but is also not evident, as there are no cloacae visible. Herrerín and Garralda (2012) report a case of LCPD with an atrophied ipsilateral tibia; the smaller diameter and shorter length of the ipsilateral tibia in the case of SHSM22 could have a similar origin. There is also a small but pronounced enthesophyte on the medial side of the proximal shaft of the left tibia.…”
Section: Discussionmentioning
confidence: 88%
“…Legg-Calvé-Perthes disease is osteochondrosis of the femoral head in children (Aufderheide and Rodríguez-Martín, 1998;Smrčka et al, 2009). It is generally accepted that this condition is produced by avascular necrosis caused by an interruption of the blood flow that reaches the epiphysis of the femoral head, especially the blood supplies from the upper and lower retinacular arteries (Aufderheide and Rodríguez-Martín, 1998;Ortner, 2003;Smrčka et al, 2009;Herrerín and Garralda, 2012). This avascular necrosis may have many different causes and the initial ischaemic episode which stops normal vascularisation is often of unknown aetiology (Smrčka et al, 2009;Herrerín and Garralda, 2012).…”
Section: Slipped Femoral Capital Epiphysis Versus Legg-calvé-perthes mentioning
confidence: 99%
“…Early severe degenerative arthritis modifies the appearance and can make differentiation from the end stage of slipped capital femoral epiphysis difficult (Ortner, 2003). The acetabulum is also deformed, becoming flatter, and wider, and showing an irregular articular surface (Herrerín and Garralda, 2012). If left untreated, restoration and remodelling of the bone fixes the 'mushroom' shape of the femoral head.…”
Section: Slipped Femoral Capital Epiphysis Versus Legg-calvé-perthes mentioning
confidence: 99%
“…It involves childhood osteochondrosis of the femoral head caused by interruption of its blood flow, leading to extensive avascular necrosis of the subchondral bone (Smrcka et al, 2009). The etiology of the initial ischemic episode that interrupts normal vascularization is unknown, although some authors have suggested a traumatic origin (Herrerín and Gallarda, 2012;Ortner, 2003). Because of the interrupted blood flow, bone resorption in the subchondral area is greater than deposition; the femoral head becomes biomechanically weak and fragmentation or pathological fracture can take place (Salter, 1999).…”
Section: Introductionmentioning
confidence: 99%